Evaluation of Cholecalciferol Efficacy in the Management of Secondary Hyperparathyroidism in Hemodialysis Patients - Hamad Ahmad Khan, Muhammad Naeem, Noman Khan Gandapur, Fouzia Jameel, Jaweria Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
The deficiency of vitamin D is public among hemodialysis (HD) patients and is a key factor in the development of secondary hyperparathyroidism (SHPT). Secondary hyperparathyroidism is currently accomplished by lowering circulating phosphate levels with parathyroid hormone (PTH), vitamin D analogs, and oral binders. The current study aim was to assess the efficacy of cholecalciferol in the management of secondary hyperparathyroidism in hemodialysis patients with concomitant vitamin D deficiency/insufficiency. A total of 53 patients were taken with25 male and 28 female patients. After treating patients with cholecalciferol, serum PTH levels improved significantly, with mean pre-treatment levels of 486.99±191.10, which had decreased to a mean post-treatment level of 301.66±201.08. Serum Vitamin D levels also improved significantly, with mean pre-treatment levels of 10.86±4.98, which increased to a mean post-treatment level of 29.98±17.24. Patients treated with cholecalciferol had no significant change in phosphorous and calcium levels. Keywords: Parathyroid Hormone; Cholecalciferol; Vitamin D; Secondary Hyperparathyroidism; hemodialysis; Pakistan